DIFFERENTIATED INSTRUCTIONS: RELEVANT STUDIES ON ITS IMPLEMENTATION - I Gusti Ayu Mirawati; Ni Komang Arie Suwastini; Novi Diah Haryanti; I Gusti Agung Sri Rwa Jayantini (Universitas Pendidikan Ganesha, 2022)
Differentiated instructions have been recommended for classrooms with students of different readiness, learning profiles, and backgrounds in English classrooms. This study aimed at elaborating the implementation of differentiated instruction in terms of its advantages and the challenges encountered by teachers and students in implementing differentiated instruction. The study was designed as library research, following George's ten steps (2008) model. Experts' opinions and previous studies were reviewed in this present study to provide a comprehensive mapping of the advantages and challenges in implementing differentiated instructions. The review revealed that differentiated instruction could motivate low-achieving students, increase students' participation, interaction, and cooperation, as well as build a better teacher-student relationship. However, differentiated instruction also poses challenges, such as time-consuming, misperception about unfair treatments, and class size. These results imply that better planning should be conducted before implementing differentiated instruction to gain its benefits.